Pengaruh Debit Air Pendingin pada Proses Flame Heating terhadap Sifat Fisis dan Mekanik Aluminium 7075 - Ghailan Wicaksana; Teguh Triyono; Nurul Muhayat (Mekanika: Majalah Ilmiah Mekanika, 2018)
Aluminum alloy 7075 is a combination that are consists of 5,5% Zn, 2,5% Mn, 1,5% Cu, 0,3% Cr and 0,2% Mn. Heat treatment phase is using flame heating method. There are 3 steps of dissolution in flame heating process. The first is heat treatment solution in the temperature between 450-500°C. The second is quenching phase using flow speed variation 1000; 1200 and 1400 cc/minute and the third phase is using aging which to hold the room temperature until reaching 120°C. Specimen test phase using vickers hardness test, micro structure and impact test. Flame heating treatment process in 1000 cc/minute quenching cause specimen become harder, using hardness test 93,43 VHN is achieved. With additional aging treatment, the hardness increase to 152,63 VHN and almost close 153,80 VHN raw material. The biggest Impact test value is gained from the result of flame heating without aging with cooling flow variation of 1000 cc/minute is 0,630 J/mm².